The effects of an online brief mindfulness activities training on the psychological functioning of medical officers : a pilot study - Ailing, Evelyn Ngui (2021)
Empirical evidence suggested that psychological interventions can be successfully delivered online. Medical officers are under high levels of stress as the main frontliners managing the COVID-19 pandemic alongside their day-to-day roles, family obligations, and research work. This study aimed to examine whether a brief mindfulness activities training for medical officers improve outcomes for depression, anxiety, stress and mindfulness. A randomized, controlled trial (RCT) was conducted at Hospital Universiti Sains Malaysia where participants were randomly assigned to one of four groups of (1) low frequency intervention group (daily session over a week), (2) medium frequency intervention group (daily session over two weeks), (3) high frequency intervention group (daily session over three weeks) or (4) the control group. Outcome measures included the Depression, Anxiety, and Stress Scale (DASS-21) and the Mindful Attention Awareness Scale (MAAS). Of the 22 participants, an increase in mindfulness, as measured by the MAAS, was found in the intervention group (p = 0.002). There was also a reduction in depression levels (p = 0.01) as measured by the DASS-21. The increase in mindfulness was observed in the low frequency and high frequency group, while the reduction of depression levels could not be observed between frequency groups. Participants self-reported increased relaxation and stress reduction. This study provides insights into the feasibility and acceptability of an online, brief mindfulness activities training for medical officers. Findings will inform the future design and implementation of larger studies.